Orchestrating internal resource management: The sensing, shielding, and shifting roles of internal audit in Ghanaian listed companies - Dawuda, Abudu; Ataribanam, Samuel; Mahama, Fuseini; Luqman, Abudu; Anyass, Salifu Mumuni Ibrahim (Asian Journal of Economics and Empirical Research, 2026)
This study reconceptualizes the internal audit function as an orchestration capability comprising sensing, shielding, and shifting roles. It examines how these roles drive effective internal resource management (IRM) and sustainable value creation in Ghana’s listed companies. A mixed-method design was employed, combining survey data from 300 principal officers across 30 listed firms with interviews conducted with internal auditors and audit committee chairs. Quantitative data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationships between orchestration capabilities and internal resource management. The results show that all three orchestration capabilities significantly enhance internal resource management. However, internal auditors place greater emphasis on shielding routines than on sensing and shifting, revealing technical skill gaps in predictive analytics and value chain analysis. These findings extend the Resource-Based View and Dynamic Capabilities Theory by positioning internal audit as a frontline strategic partner. Capacity building in analytics, real-time monitoring, and value chain tools is needed to enable internal auditors to evolve beyond compliance toward proactive resource orchestration. Enhancing the internal audit’s orchestration role would promote efficient resource use, resilience, and long-term value creation, thereby strengthening economic sustainability.